A highly sensitive endotoxin sensor based on redox cycling in a nanocavity. Issue 11 (10th May 2019) - Ito, Kentaro; Inoue, Kumi Y.; Ino, Kosuke; Matsue, Tomokazu; Shiku, Hitoshi
Abstract : A highly sensitive endotoxin sensor and novel analytical principle using diffusion coefficient difference was developed using a nanocavity device. Abstract : We report a highly sensitive and rapid electrochemical method for the detection of endotoxin, based on a Limulus amebocyte lysate (LAL) assay using redox cycling at a pair of electrodes in a nanocavity for electrochemical signal amplification. We have previously developed Boc-Leu-Gly-Arg- p -aminophenol (LGR-pAP) as a substrate for the amperometric LAL assay, and in this work, Z-Leu-Gly-Arg-aminomethylferrocene (LGR-AMF) was newly prepared. They were examined as substrates for a LAL-based endotoxin assay using a nanocavity device. During the last step of the endotoxin-induced LAL cascade reaction, pAP or AMF is generated from the substrate, which can be detected electrochemically with efficient signal amplification by redox cycling between the two electrodes in the nanocavity. A device with a 190 nm-high nanocavity was fabricated by photolithography. With the fabricated device in model assay solutions prepared by mixing LGR-pAP and pAP, we demonstrated that pAP could be quantitatively detected from the difference in oxidation potentials between LGR-pAP and pAP. For LGR-AMF and AMF, a difference in the formal potential of 0.1 V was obtained which was considered to be insufficient to distinguish AMF from LGR-AMF. However, we showed for the first time that analytes such as AMF can be detected by differences in diffusion coefficients between the analyte and coexisting molecules (such as LGR-AMF) using a device with high redox-cycling efficiency. Next, the endotoxin assay was performed using the fabricated nanocavity device. Using this method, endotoxin was detected at concentrations as low as 0.2 and 0.5 EU L −1 after LAL reaction times of 1 h and 30 min, respectively, using the LGR-pAP substrate. However, the endotoxin assay using LGR-AMF was not successful because the clotting enzyme did not react with LGR-AMF. This problem might be solved by further design of the substrate. Our nanocavity device represents an effective platform for the simple and rapid detection of endotoxin with high sensitivity.